Institutional Quality in Attracting Foreign Direct Investment to Small Countries - Abdul Wahab, Effiezal Aswadi; Masron, T.; Naseem, N. (Persatuan Ekonomi Malaysia, 2018)
Institutional quality (IQ) has been proven by many studies as generating positive impact to economic development, including via luring more foreign direct investment (FDI) inflows. However, the inconsistent reality relating to FDI inflows and IQ of the host countries, especially in small countries has led this study to re-examine the effectiveness of IQ in promoting FDI inflows. Hence, selecting small countries in four regions located around four large countries, namely Brazil, Russia, India and China (BRIC) as a case study, results confirmed that the effectiveness of IQ is gradually eroded if IQ in BRIC is also relatively improved.